Comparison of laparoscopic partial nephrectomy performed with AirSeal® system vs. standard insufflator: results from a referral center - Flavio Forte; Domenico Tripodi; Daniele Pironi; Emanuele Corongiu; Federica Gagliardi; Marco Frisenda; Gaetano Gallo; Antonia Quarantiello; Giuseppe Di Lorenzo; Yuri Cavaleri; Stefano Salciccia; Eleonora Lori; et al. (Frontiers in Surgery, 2023)
ObjectiveTo compare perioperative and oncologic surgical outcomes during laparoscopic partial nephrectomy (LPN) performed by standard carbon dioxide insufflation, with those from surgeries in which the AirSeal® intelligent insufflation system was used for renal tumors.Materials and methodsA total of 27 patients with renal tumor were identified, 14 underwent LPN with AirSeal® (group A) and 13 LPN with standard insufflator (group B), respectively. Demographic baseline characteristics were similar in the two groups.ResultsThe size of the tumor was largest in group B (29.64 vs. 32.1 mm). The mean operative time was shorter in the AirSeal® group [group A: mean 109.0 min, median 107.5 min, interquartile range (IQR) 85; group B: mean 121.0 min, median 120.0 min, IQR 50.0]. Positive margin rates were absent in the two groups. Estimated blood loss presented a difference in the perioperative period (group A: mean 1.5 g/dL, median 1.45 g/dL; group B: mean 2.15 g/dL, median 2.2 g/dL). Time to ischemia was found to be shorter in group A with a median of 18 min compared to a median of 20 min in group B. No subcutaneous emphysema, pneumothorax, and pneumomediastinum cases occurred in either group. A postoperative complication developed in one patient requiring superselective embolization.ConclusionIn selected patients, our preliminary surgical experience has shown that the LPN procedure performed with the aid of the AirSeal® intelligent insufflation system can be used to treat even medium-/high-complexity kidney lesions, with a reduction in operating times, lower rates of complications, and perioperative blood loss.Clinical trial registrationAirSealV1.